#128 : Is Non-Closure Suitable as a Skin Closure Technique for 5 mm Laparoscopic Port-Site? - A Randomised Controlled Trial of Non-Closure Versus Transcutaneous Suture - Mukhri Hamdan; Nusaibah Zulkifli (Fertility & Reproduction, 2023)
Background and Aims: Laparoscopy has become the access of choice even in complex abdomino-pelvic surgery cases and more abdominal access ports have been used to assist with the surgery. Systematic review done on skin closure of 5 mm laparoscopic port-site showed comparable outcome between sutured and sutureless technique. Transcutaneous suture is better than subcuticular suture in the sutured group sub-analysis. No RCT were found comparing skin closure versus non-closure technique using simple dressing only. Method: Randomised controlled trial – non superiority in Gynaecology Department, University Malaya Medical Centre in 2019. Based on power calculation, 40 subjects are needed. Each patient act as their own control – each will receive NC and TS for comparison. 40 patients (n=80) were included for final analysis. The 5 mm port site will be assigned with skin closure using NC versus TS where the surgical incision wound is covered with routine dressing after the operation. The primary outcome is the scar appearance at day 90 from the patient and blinded surgeons’ point of view. Secondary outcomes are patient satisfaction and pain at day 14, and wound complications. Results: Cosmetic outcome in terms of scar appearance at day 90 showed no difference between NC and TS rated by the patient (MD 5.25 [0.07, 10.57], p 0.053) and the surgeon (MD 0.88 [0.08, 1.83], p 0.07). Pain is better perceived in NC group (MD 3.6 [0.19, 6.96], p 0.039) and patient satisfaction at day 14 is also better in NC group (MD 11.8 [4.18, 19.33], p 0.03). There was no significant difference in terms of wound complications and no surgical site infection were observed in both groups. Conclusion: NC and TS techniques have comparable cosmetic outcome and wound complications. Pain perception is better in NC than TS.